2011
DOI: 10.3851/imp1942
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Silibinin as ‘Rescue Treatment’ for On-Treatment Non-Responders to Pegylated Interferon/Ribavirin Combination Therapy

Abstract: ivSIL is an effective 'rescue treatment' for on-treatment non-responders to full-dose of SOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…Consequently, its effectiveness in hepatitis C treatment is being investigated in several centers. Promising outcomes have been reported after silibinin treatment of chronic hepatitis C nonresponders (Ferenci et al, 2008;Biermer and Berg, 2009;Rutter et al, 2011). A positive effect of silibinin administration on hepatitis C was also observed in patients undergoing liver transplantation, in whom silibinin prevents reinfection after transplantation (Neumann et al, 2010;Beinhardt et al, 2011;Eurich et al, 2011;Rutter et al, 2011;Marino et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consequently, its effectiveness in hepatitis C treatment is being investigated in several centers. Promising outcomes have been reported after silibinin treatment of chronic hepatitis C nonresponders (Ferenci et al, 2008;Biermer and Berg, 2009;Rutter et al, 2011). A positive effect of silibinin administration on hepatitis C was also observed in patients undergoing liver transplantation, in whom silibinin prevents reinfection after transplantation (Neumann et al, 2010;Beinhardt et al, 2011;Eurich et al, 2011;Rutter et al, 2011;Marino et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Promising outcomes have been reported after silibinin treatment of chronic hepatitis C nonresponders (Ferenci et al, 2008;Biermer and Berg, 2009;Rutter et al, 2011). A positive effect of silibinin administration on hepatitis C was also observed in patients undergoing liver transplantation, in whom silibinin prevents reinfection after transplantation (Neumann et al, 2010;Beinhardt et al, 2011;Eurich et al, 2011;Rutter et al, 2011;Marino et al, 2013). Although administration of silibinin was generally well tolerated, a significant increase in serum bilirubin levels was reported in several studies (Neumann et al, 2010;Beinhardt et al, 2011;Rutter et al, 2011;Marino et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…In addition to its well-known hepatoprotective effects, a panel of other pharmacological activities of silybin, such as anti-cancer, has been recently reported (Zhou et al, 2008;Rajamanickam et al, 2010;Ravichandran et al, 2010;Ramasamy et al, 2011). Although silymarin and silybin are known to be safe and well-tolerated (Rutter et al, 2011;Marino et al, 2013;Zhu et al, 2013), hyperbilirubinemia caused by repressed UGT1A1 enzyme activity has been notified as a potential toxic effect (Flaig et al, 2007;Parveen et al, 2011;Rutter et al, 2011;Polyak et al, 2013;Sumida et al, 2013). Moreover, a critical concern about the use of silybin is the potential drug-drug interactions (DDI) because silybin is in most cases used in combination with a variety of other pharmaceutics.…”
Section: Introductionmentioning
confidence: 99%
“…is an important enzyme in the metabolism of bilirubin, and that the inherited mutation of UGT1A1 resulted in complete or partial enzyme inaction, which is the principal cause of newborn Crigler-Najja syndrome and Gilbert syndrome, characterized with severe and mild hyperbilirubinemia, respectively (Flaig et al, 2007;Parveen et al, 2011;Rutter et al, 2011;Polyak et al, 2013). Indeed, it has been previously reported that patients receiving silybin treatment at high dose were characterized with increased plasma levels of bilirubin.…”
mentioning
confidence: 99%
“…Much attention has been given to the potential health-promoting properties of flavonoids due to their reported wide range of activities in the prevention of common diseases, including coronary heart disease, cancer, neurodegenerative disease, gastrointestinal disorders and others. [16][17][18] Information on the potential benefits of flavonoids in the treatment of hepatitis C is relatively limited and sometimes contradictory, 19,20 although some flavonoids, including quercetin, one of the most abundant flavonol-type flavonoids present in the human diet, seem to inhibit the replication of HCV. [21][22][23] On the basis of these data, in the current research we explored the effects of different natural antioxidant flavonoids on HCV replication in an in vitro model.…”
mentioning
confidence: 99%